2002
DOI: 10.1016/s0893-133x(01)00394-3
|View full text |Cite
|
Sign up to set email alerts
|

A Gender-Specific Association between the Serotonin Transporter Gene and Suicide Attempts

Abstract: This pilot study tested the gender-specificity of the association between suicide attempts and a polymorphism in the promoter area of the serotonin transporter with two allelic variants, a long (1) variant and a short (s) variant. In aSuicide attempts, in more than 90% of the cases, are associated with mental disorders. Vulnerability to suicide is probably best understood in the context of Mann's model of stress-diathesis (Mann et al. 1999). Low brain serotonergic function appears to be undeniably related to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 13 publications
1
23
1
Order By: Relevance
“…It was demonstrated that the frequencies of the 5-HTTVNTR genotypes were not associated with the presence of suicidal history. Although, to our knowledge, no association study of suicidal behavior and the 5-HTTVNTR polymorphism has been reported, a positive association has been demonstrated between 5-HTTLPR and suicidal behavior in a number of investigations of another 5-HTT polymorphism [e.g., 35,36], albeit not all [e.g., 37,38].…”
Section: Discussionmentioning
confidence: 88%
“…It was demonstrated that the frequencies of the 5-HTTVNTR genotypes were not associated with the presence of suicidal history. Although, to our knowledge, no association study of suicidal behavior and the 5-HTTVNTR polymorphism has been reported, a positive association has been demonstrated between 5-HTTLPR and suicidal behavior in a number of investigations of another 5-HTT polymorphism [e.g., 35,36], albeit not all [e.g., 37,38].…”
Section: Discussionmentioning
confidence: 88%
“…Seven of these studies failed to demonstrate any link between suicidal behavior and SERT genotype or 5-HTTLPR allele frequency (Ohara et al, 1998;Chong et al, 2000;Geijer et al, 2000;Ho et al, 2000;Mann et al, 2000;Fitch et al, 2001;Rujescu et al, 2001). The remaining seven studies all found some association, albeit with differing results (Du et al, 1999;Bellivier et al, 2000;Bondy et al, 2000;Gorwood et al, 2000;Russ et al, 2000;Courtet et al, 2001;Baca-Garcia et al, 2002). One study demonstrated a higher frequency of the l allele in depressed suicide victims compared to nonsuicidal controls (Du et al, 1999).…”
Section: Genetics Of Sertmentioning
confidence: 98%
“…The internal consistency of the planning subscale was somewhat lower, α = 0.71 for the first sample and α = 0.69 for the second sample (α = 0.70 for the combined sample). Table 4 shows that the scores of the total SIS and expected lethality subscale were significantly higher in the [2] 0.19 0.57 Precautions [3] 0.21 0.52 Act to get help [4] 0.46 0.07 Final acts [5] -0.10 0.52 Active preparation [6] 0.04 0.72 Note [7] -0.04 0.58 Communication [8] -0.09 0.44 Purpose of attempt [9] 0.71 -0.03 Expectations of fatality [10] 0.84 -0.04 Concept of lethality [11] 0.79 -0.03 Seriousness [12] 0.82 0.05 Ambivalence to living [13] 0.71 0.04 Concept of rescuability [14] 0.65 -0.01 Degree of premeditation [15] 0.24 0.50 * Loadings greater than 0.4 are underlined.…”
Section: S Sis Subscalesmentioning
confidence: 99%